EXPERIMENTAL STUDY OF LOCAL BEHAVIOR OF STRENGTHENED REINFORCED CONCRETE SHORT CORBEL BY BONDING CARBON FIBER FABRICS - SRAVAN, KUMAR ADIMALLA; VADTHYA, SRINIVAS (The journal of contemporary issues in business and government, 2020)
Most of the structures in civil Engineering, after 50 years old, meet the current safety standards or have excessive cracks. Steel corrosion may also cause the occurrence of high deflection or instability of the structure itself. It is generally manifested by poor performance under service loading in the form of excessive deflections or cracking. The introduction about 34 years ago of composite materials in the field of Civil Engineering allows other strengthening orrepair of reinforced concrete structures by bonding composite carbon fiber fabrics (Abdul Wahab, 1989; ACI, 2000; Chris, 2007). Carbon fiber materials have many advantages (Ivanova, 2013): their weight, flexibility, implementation easier and also their physicochemical properties (corrosion) interesting. This technical of strengthening compensate the loss of rigidity and resistance to cracking due to the strengthening and improving performance and durability of structures.Corbel is one important element of structureto support the pre-cast structural system such as pre-cast beam and pre-stressed beam (Anis, 2012 and Rejane, 2005). The corbel is cast monolithic with the column element or wall element. It is interesting to study the local mechanical behavior of this very short element of the structure using carbon fiber materials (Mohammed, 2005; Futtuhi, 1987; Gampione, 2005; Erfan, 2010). This paper is mainly interested in the study of three types of reinforcement: by bonded carbon fiber fabrics, wrapping of carbon fabrics and by bonding plate in shear area, under flexural bending. Local deformation using strain gauges to measure strains in the steel, concrete and carbon fiber sheets of strengthened reinforced concrete short-corbel, is also investigated. In this investigation, deformations, cracking modes and collapse mechanism are studied.